Visualizing cognitive load and mnemonic encoding: a comparative QEEG study on traditional lecturing and digital multimedia instruction - Zelvira, Brithania; Gea Pandhita S; Erlin Listiyaningsih (Sanus Medical Journal, 2025)
Background. Various teaching strategies impact cognitive functions differently. These methods influence concentration and attention, crucial for information assimilation, processing, and retrieval. This research examines the influence of lecture-based and video-based learning on primary school students' brain activities, using Quantitative Electroencephalogram (QEEG) analysis. Method. The study involved 36 children aged 10-12 years, including 17 boys and 19 girls. Quantitative Electroencephalogram (QEEG) recordings were obtained using the EMOTIV EPOC 14-Channel device. The analysis focused on the frontal, temporal, occipital region, examining delta, theta, alpha, beta, high-beta, beta-1, beta-2, and beta-3 brainwaves. These waveforms were normalized to Z-Scores for comparison. Statistical differences between groups were assessed using t-tests.Result. Post-lecturing and video-based learning, QEEG analyses revealed an enhancement in beta-2 wave activity at F3 and F7 locations. Increase beta wave, suggesting differentiated cognitive engagement patterns between the two learning modalities. Conclusion. Lecturing and video-based learning enhance cognitive engagement, evidenced by elevated alfa and beta wave activity. Lecturing elicits stronger concentration and executive function responses, positioning it as a preferred approach for tasks demanding significant verbal processing and motor planning. Meanwhile showed higher emotional expression, emotional memory, and visual processing activity. Latar Belakang. Berbagai strategi pengajaran memengaruhi fungsi kognitif secara berbeda. Metode-metode ini memengaruhi konsentrasi dan perhatian, yang sangat penting untuk asimilasi, pemrosesan, dan pengambilan informasi. Penelitian ini mengkaji pengaruh pembelajaran berbasis ceramah dan berbasis video terhadap aktivitas otak siswa sekolah dasar, menggunakan analisis Elektroensefalogram Kuantitatif (QEEG). Metode. Studi ini melibatkan 36 anak berusia 10-12 tahun, termasuk 17 laki-laki dan 19 perempuan. Rekaman Elektroensefalogram Kuantitatif (QEEG) diperoleh menggunakan perangkat EMOTIV EPOC 14-Channel. Analisis difokuskan pada daerah frontal, temporal, dan oksipital, dengan memeriksa gelombang otak delta, theta, alpha, beta, high-beta, beta-1, beta-2, dan beta-3. Gelombang-gelombang ini dinormalisasi ke Z-Score untuk perbandingan. Perbedaan statistik antar kelompok dinilai menggunakan uji-t.Hasil. Setelah perkuliahan dan pembelajaran berbasis video, analisis QEEG mengungkapkan peningkatan aktivitas gelombang beta-2 di lokasi F3 dan F7. Peningkatan gelombang beta menunjukkan pola keterlibatan kognitif yang berbeda antara kedua modalitas pembelajaran tersebut.Kesimpulan. Perkuliahan dan pembelajaran berbasis video meningkatkan keterlibatan kognitif, dibuktikan dengan peningkatan aktivitas gelombang alfa dan beta. Perkuliahan memicu konsentrasi dan respons fungsi eksekutif yang lebih kuat, menjadikannya pendekatan yang lebih disukai untuk tugas-tugas yang membutuhkan pemrosesan verbal dan perencanaan motorik yang signifikan. Sementara itu, menunjukkan ekspresi emosional, memori emosional, dan aktivitas pemrosesan visual yang lebih tinggi.